On Living Alone with Alzheimer’s Disease - PORTACOLONE, E. (Care Wkly, 2018)
A sociologist’s encounters with a retired executive living alone with Alzheimer’s disease reveal gaps in the U.S. healthcare system. These gaps emerge during eight ethnographic interviews and participant observation between 2014 and 2017 with Ms. Judith Banks, 79. Ms. Banks’ perspective offers an inside-view of the challenges of living alone with cognitive impairment. Receiving a diagnosis of Alzheimer’s disease was “brutal” for her and the support to continue living in the community almost non-existent. Gaps in the U.S. healthcare system further emerge from the contrast between Ms. Banks’ case study and the examination of the Danish system of care for non-institutionalized persons with dementia. Given that one third of people with dementia live alone in the U.S. and that they are likely to experience poorer health outcomes than counterparts living with others, it is critical to ensure that they receive appropriate health services upon diagnosis of cognitive impairment.